2020
DOI: 10.1136/bjophthalmol-2020-317322
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of microvascular perfusion and neurodegenerative changes in early type 2 diabetic retinal disease

Abstract: AimTo prospectively monitor subclinical changes in capillary perfusion and retinal layer thickness in patients with type 2 diabetes and early diabetic retinal disease over 2 years.MethodsIn this longitudinal study we performed biannual retinal vascular imaging using optical coherence tomography angiography (RTVue) to analyse the foveal avascular zone (FAZ) area, perimeter, acircularity index (AI) and parafoveal superficial/deep vessel density (VD). Spectral-domain optical coherence tomography (Spectralis) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 29 publications
4
25
1
Order By: Relevance
“…Additionally, this study shows that thinning persisted after controlling for the many confounding factors associated with retinal thickness measurements, and after excluding participants with DM who had more than mild DR. These findings are consistent with our prior findings from 45 participants with Type 1 DM where we showed progressive GC-IPL thinning over time and those of Aschauer et al showing GC-IPL thinning but no mRNFL thinning over time among patients with Type 2 DM [ 6 , 24 ]. A recent meta-analysis on this topic also showed a stronger association with GC-IPL thickness compared to mRNFL thickness between DM patients with no DR and controls [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, this study shows that thinning persisted after controlling for the many confounding factors associated with retinal thickness measurements, and after excluding participants with DM who had more than mild DR. These findings are consistent with our prior findings from 45 participants with Type 1 DM where we showed progressive GC-IPL thinning over time and those of Aschauer et al showing GC-IPL thinning but no mRNFL thinning over time among patients with Type 2 DM [ 6 , 24 ]. A recent meta-analysis on this topic also showed a stronger association with GC-IPL thickness compared to mRNFL thickness between DM patients with no DR and controls [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Pooling the findings of those with DRN and those without DRN may be minimizing the overall differences in layer thickness between groups. Irrespective of the exact reasons for this finding, our results as well as that of others [ 24 ] suggest that GC-IPL thickness may be a more robust marker of early DRN changes compared to mRNFL.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It is very likely that the early neuronal and vascular changes in the diabetic retina are tightly coupled and dissecting the timeline of onset may continue to prove challenging. Indeed, a prospective longitudinal study of patients with type 2 diabetes demonstrated progressive decrease in the superficial vascular density along with thinning of the GCL and IPL over a two-year period, suggesting that these changes occur in parallel [ 79 •]. Kim et al also described a similar association between microvascular changes and inner retinal thinning in a retrospective analysis of 40 diabetic eyes without DR, highlighting the importance of neurovascular coupling in the retina [ 80 ].…”
Section: Does Neurodegeneration Precede Vascular Changes?mentioning
confidence: 99%
“…A previous study quantified a set of the neurovascular parameters of OCTA related to the severity of DR, which might have potential clinical applications for DR staging ( 11 ). Previous longitudinal studies have shown that the microangiopathy and neurodegeneration appear in parallel and are highly progressive even in the early stage of DR ( 13 ), but few studies explored these features following PRP. To the best of our knowledge, the comprehensive retinal vascular and neural changes in the macular and peripapillary area and subfoveal choroidal thickness (SFCT) changes after PRP have not been reported.…”
Section: Introductionmentioning
confidence: 99%